Influence of the Electric Field on the Electronic Properties of the Substituted Biphenyl Molecules - O.A. Shovkoplyas; Y.M. Lopatkin; P.O. Kondratenko (Журнал нано- та електронної фізики)
This paper presents the results of investigations into the influence of the longitudinal and transverse electric field on the potential surface, the dipole moments and electronic spectra of the substituted biphenyl molecules that can be regarded as the elements of nanoelectronics.